UPAYA MEMINIMALISIR DAMPAK LINGKUNGAN DARI PENGGUNAAN PESTISIDA DALAM PERTANIAN (DAMPAK LINGKUNGAN DAN PENANGGULANGANNYA) - Jayanti , Hadis; Suprapta , Dewa Ngurah (Agriculture Faculty of Flores University, 2009)
Utilization of synthetic pesticide seems up to now remains to be one of the methods in controlling pest and plant disease because it plays a role in determining the quality and quantity of the crops. Improver of synthetic pesticide in agriculture can adversely affect the ecosystem such as water and soil pollution. The occurrence of pest resistance, the outbreak of secondary pest, the resurgence of pest, the death of predators, the residue of pesticide in food, and the pesticide residue that affects man's health. Although it has been widely known that pesticide has a bad impact on the environment, the use of pesticide is still needed in agricultural practice. Its use needs to pay attention to the concept of Integrated Pest Management in which the use of pesticide is only made when it is absolutely necessary, that is, when the population of pest increases and lies above one level of the pest population, the Economic Threshold (Untung, 1993). To know the safety level of pesticide, evaluation of toxicity of a pesticide is needed and it is commonly tested in the animal of high level. This is done in such a way that the toxicity and safety level of the pesticide can be known by farmers, users of pesticide, and the environment. Based on the information on the toxicity level, it is expected that the steps of environmental management can be taken to minimize the negative impact of pesticide. The effort of minimizing the negative impact of pesticide can be done in a variety of ways. For example, the direction was given to the users in terms of giving the dosage, application time, safe working procedure, choosing pesticide with the precise target, choosing a pesticide that can decompose easily, application target, a time before harvest, tool and exact application technique, keeping as small pollution as possible. In the future, it is hoped that the use of pesticide will decrease and will be more selective, and supported by new inventions in the technology of processing pesticide disposal and the technology of utilizing botanical pesticide which is all expected to be effective in overcoming the disturbance of pest and plant disease at the same time minimizing environmental degradation.